Szanse rozwoju turystyki z wykorzystaniem polskich zamków i pałaców w Euroregionie Karpackim - Bytnar, Renata (Opportunities for the Development of Tourism Taking Advantage of Polish Castles and Palaces in the Karpacki Euroregion, 2005)
The chances of the tourism development thanks to the usage of Polish castles and palaces in the Podkarpacie Euroregion. The Podkarpackie region is the only area in Europe with so many exceptional attraction, both natural and cultural. Those attractions are potentials, which if used properly (protected, promoted, managed and developed) might become the main factor in the development for the people living in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 110-116